Definisi Kembali Business Process Penjualan Ritel Akibat Pengaruh Teknologi Informasi - Andi Fuji Rahman (Jurnal Ekonomi, 2018)
Living within internet become easier, back to 90 or earlier when need something we have to go shop to buy something we needed. But now these days, we just picked the phone make a phone call to shop and make an order. Just couple hours the product we are needed just arrived right front our house, pick the product and pay the cash. Everything become very simple. Internet era make us to redefinition of Business Process of sales. Back to earlier, the buyer and the sales have to meet make transaction. But they don’t have to meet again, and the matter fact, they don’t know to each other completely. Now the transaction support by internet and bank, they make this impossible. Internet make people (buyer and sales) meet in web world, the make transaction. And finally the buyer pay the price via bank and again the buyer pay the price via internet through the bank. And the sales after received confirmation from the bank, they right the way to pack the package and delivery the package from courier service. Data of year 2013-2013 average increment of direct sales only grows amount 9.9% and increment of sales online grows up to 59.9. it seem increment of sales of online very massive in period year 2013 up to 2017, and the number sales of online almost half of direct sales i.e. 2019 T and sales of online i.e 108 T. With regression coefficient formula look relationship direct sales with increment of Indonesia’s growth economy i.e. 0.212% and sales online growth i.e. 0.223% , it means both sales online and direct sales have one direction refer to Indonesia’s economy growth, only sales online has stronger relationship i.e. 0.223% and gap 0.011% compare to direct sales.